Prohibition of Monopolistic Practices and Unfair Business Competition in Indonesia: A Legal Mechanism to Balance the Public Interest - Mahendrawati, Ni Luh Made (International Journal of Criminology and Sociology, 2021)
The study is to explore the legal mechanism of prohibition of monopolistic practices and unfair business competition in Indonesia by looking at the role of the Business Competition Supervisory Commission (KPPU). This study was conducted using the empirical normative method. In this context, the regulatory reference used is Law No. 5 of 1999 (Anti-Monopoly Law). Other regulations are Article 34 of Law No. 5 of 1999 and Presidential Decree No. 75 of 1999 and named the Business Competition Supervisory Commission (KPPU). Several KPPU decisions analyzed were in the cities of Medan, Semarang, Surabaya, Makassar and Central Jakarta. The results showed that Law No. 5 of 1999 regarding the Prohibition of Monopolistic Practices and Unfair Business Competition in Indonesia was formulated to the principle of balancing interests, namely the balance between the interests of business actors with the public interest. The formulation of the principle of balance can be found in the considerations, explanations and articles in Law No. 5 of 1999.